Obstacles in the Implementation of Islamic Religious Education in Indonesian Schools: Analysis of Suboptimal Learning - Ananda Siddik; Juliani; Dinda Anggraini; Dinda Aldini; Desi Lestari (Yayasan Zia Salsabila, 2024)
Islamic Religious Education (PAI) plays an important role in forming the character and morals of students in Indonesia. However, its implementation often encounters various obstacles which cause PAI learning to be less than optimal. This research aims to analyze the obstacles that exist in implementing PAI in Indonesian schools, with a focus on aspects of learning that are not optimal. This research uses a qualitative approach with a case study method in several schools in Indonesia, which involves interviews with PAI teachers, students, and school officials, as well as direct observation of the learning process. The research results show that there are several significant obstacles in implementing PAI, including the lack of competence of PAI teachers, limited educational resources, and a lack of appropriate learning support facilities. Apart from that, low student motivation factors, the influence of the family and social environment, and limited time allocated for PAI in the curriculum also contribute to less-than-optimal learning. This research reveals that although PAI has a strategic role in education, external and internal factors in schools need to receive more attention so that the learning process can run effectively. Therefore, this research recommends increasing training for PAI teachers, providing adequate facilities, and strengthening the role of parents and the community in supporting religious learning in schools.